Performance monitoring algorithm for optimizing electrical power generated by using photovoltaic system - Pradeep, M.V.K. (American Institute of Physics Inc., 2016)
Demand for electricity in Malaysia has seen a substantial hike in light of the nation's rapid economic development. The current method of generating electricity is through the combustion of fossil fuels which has led to the detrimental effects on the environment besides causing social and economic outbreaks due to its highly volatile prices. Thus the need for a sustainable energy source is paramount and one that is quickly gaining acceptance is solar energy. However, due to the various environmental and geographical factors that affect the generation of solar electricity, the capability of solar electricity generating system (SEGS) is unable to compete with the high conversion efficiencies of conventional energy sources. In order to effectively monitor SEGS, this study is proposing a performance monitoring system that is capable of detecting drops in the system's performance for parallel networks through a diagnostic mechanism. The performance monitoring system consists of microcontroller connected to relevant sensors for data acquisition. The acquired data is transferred to a microcomputer for software based monitoring and analysis. In order to enhance the interception of sunlight by the SEGS, a sensor based sun tracking system is interfaced to the same controller to allow the PV to maneuver itself autonomously to an angle of maximum sunlight exposure. Â© 2016 Author(s).